Securing IoT monitoring device using PUF and physical layer authentication - Zheng, Yue (2018)
IoT is rapidly becoming a reality. Forecasts predict more than 20 billion connected devices in 2020. These devices bring many benefits, but securing them in IoT environment can be a quandary. With the advent of technology, it is very easy for an adversary to clone a device and replace it, or tamper the data. In the context of wireless communications in IoT, the definition of message authentication should be extended to include verification of the device along with the integrity of the message it produced. In this paper we propose a device- and data-dependent physical layer authentication scheme by using a device-specific, dynamically variable key to generate a data-dependent tag. This tag is embedded in the data transmission using an information hiding scheme to reliably extract it at the receiver, and without compromising the performance of the underlying wireless communication system. Simulation results show that our scheme can achieve high authentication rate while rejecting the tampered transmissions in typical noisy communication channel.